A novel synthesis of 2-((2-oxopropyl)selanyl) benzamide derivatives by cascade selenenylation-acylation reaction and in vitro cytotoxicity evaluation. Issue 48 (26th November 2020) - Feng, Shuxiao; Qi, Kaiyan; Guo, Yafei; Wang, Junling; Gu, Guangna; Liu, Pu; Ma, Junying; Qu, Lingbo; Zhang, Shouren
Graphical abstract: Abstract: Based on the Se-N bond modify strategy emerging from ebselen, a facile, solvent-free cascade selenenylation-acylation reaction for synthesis of novel 2-((2-oxopropyl)selanyl) benzamide organoselenium compounds was developed, by using 2-chloroselenobenzoyl chloride as biselectrophile reagent, where acetone as primary nucleophile for the selenenylation reaction, and amine as secondary nucleophile for the acylation. In vitro cytotoxicity was evaluated by using CCK8 assay, and some of the newly synthesized compounds exhibited equally or superior activities to cisplatin against five cancer cell lines, including A549, EC109, HCT116, HepG2, and MCF-7.